Automated proof of mixed trigonometric-polynomial inequalities. (November 2020) - Chen, Shiping; Liu, Zhong
Abstract: This paper presents an algorithm for automated proof of inequalities involving a certain class of generalized polynomials where the monomials contain one variable and trigonometric functions applied to the same variable. Through Taylor Expansion, the proving of the target inequality is reduced to the verification of a series of polynomial inequalities with only one variable, and then completed by algebraic inequality-proving package such as BOTTEMA. The algorithm is complete and experiments show that it is very effective for trigonometric-polynomial inequalities, furthermore, the procedure is 'readable'.